When do plant radiations influence community assembly? The importance of historical contingency in the race for niche space. Issue 2 (13th March 2015) - Tanentzap, Andrew J.; Brandt, Angela J.; Smissen, Rob D.; Heenan, Peter B.; Fukami, Tadashi; Lee, William G.
Summary Plant radiations are widespread but their influence on community assembly has rarely been investigated. Theory and some evidence suggest that radiations can allow lineages to monopolize niche space when founding species arrive early into new bioclimatic regions and exploit ecological opportunities. These early radiations may subsequently reduce niche availability and dampen diversification of later arrivals. We tested this hypothesis of time‐dependent lineage diversification and community dominance using the alpine flora of New Zealand. We estimated ages of 16 genera from published phylogenies and determined their relative occurrence across climatic and physical gradients in the alpine zone. We used these data to reconstruct occupancy of environmental space through time, integrating palaeoclimatic and palaeogeological changes. Our analysis suggested that earlier‐colonizing lineages encountered a greater availability of environmental space, which promoted greater species diversity and occupancy of niche space. Genera that occupied broader niches were subsequently more dominant in local communities. An earlier time of arrival also contributed to greater diversity independently of its influence in accessing niche space. We suggest that plant radiations influence community assembly when they arise early in the occupancy of environmental space, allowing them to exclude later‐arriving colonists from ecological communities by niche preemption.